Pars Plana Capsulectomy with Scissors and Micro Forceps: A Case Report of an Alternative Approach for Membranous Posterior Capsule Opacity - Canleblebici, Mehmet; Yıldırım, Hakan; Erdag, Murat; Balbaba, Mehmet (My University, 2022)
Pediatric eye injuries are the leading cause of unilateral blindness in childhood. Post-traumatic cataract development is commo n, and the risk of posterior capsule opacity occurrence is seen at a high rate. Nd-YAG laser capsulotomy or anterior vitrectomy may useful, but some patients develop thick posterior membranous capsule opacity and mentioned techniques may not be performed. A 6-year-old girl who had a corneal tear repair, traumatic cataract and thick posterior capsule membrane, which could not be cleared by Nd-YAG laser or vitrectomy, was re- moved with scissors and micro forceps through the pars plana vitrector entrances. Here, we present a case report as an alternative method of pos- terior capsulectomy.
Keywords: Patoloji; Göz Hastalıkları; Cerrahi